Perbandingan Mode Naratif Apokaliptik dalam Teks Mosalaparwa dan Cariyos Dajal - Habibah, Nurmalia (Masyarakat Pernaskahan Nusantara, 2023)
This article aims to demonstrate how cultural heritage can surprisingly bridge differences that often trigger religion-based conflicts, showcasing the underlying essence of unity in diversity by delving into the interpretation of literary works. At a more specific level, this paper endeavors to uncover the universality of the Javanese perspective on the eschatological crisis culminating in the Judgment Day event. This exploration is conducted through a meticulous analysis of the apocalyptic narrative style found in two Javanese texts; the Old Javanese Mosalaparwa and the New Javanese Cariyos Dajal. When considering the conclusion of each narrative, in accordance with Collins' classification (2014) of the apocalyptic genre, Mosalaparwa falls into the historical apocalypses sub- type, while Cariyos Dajal aligns with the apocalypses involving heavenly journeys sub-type. === Tulisan ini bertujuan untuk mengungkap universalitas pandangan masyarakat Jawa terhadap krisis eskatologis yang berujung pada peristiwa kiamat melalui close reading terhadap perbandingan mode naratif apokaliptik dalam teks Mosalaparwa Jawa Kuna dan Cariyos Dajal. Setelah kedua teks kisah hari akhir dalam ranah sastra Jawa tersebut dicermati, terdapat bagian-bagian naratif yang membentuk struktur teks dan mencerminkan karakteristik apokaliptik sehingga teks-teks religius lokal itu dapat ditempatkan dalam kategori teks sastra bermode naratif apokaliptik. Apabila melihat akhir ceritanya, maka merujuk pada klasifikasi genre apokaliptik menurut Collins (2014), teks Mosalaparwa termasuk ke dalam sub-tipe historical apocalypses dan teks Cariyos Dajal ke dalam apocalypses with heavenly journeys.